2014
DOI: 10.1111/ina.12171
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bias with the single‐zone assumption in measurement of residential air exchange using the perfluorocarbon tracer gas method

Abstract: Residential air exchange rates (AERs) are vital in understanding the temporal and spatial drivers of indoor air quality (IAQ). Several methods to quantify AERs have been used in IAQ research, often with the assumption that the home is a single, well-mixed air zone. Since 2005, Health Canada has conducted IAQ studies across Canada in which AERs were measured using the perfluorocarbon tracer (PFT) gas method. Emitters and detectors of a single PFT gas were placed on the main floor to estimate a single-zone AER (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…When the whole dwelling is considered as a single zone, errors arise from the assumption that the CO 2 concentrations in other bedrooms are consistent with those of the measured space. A study found that the error from the single and well‐mixed air zone assumption could be 16% …”
Section: Discussionmentioning
confidence: 99%
“…When the whole dwelling is considered as a single zone, errors arise from the assumption that the CO 2 concentrations in other bedrooms are consistent with those of the measured space. A study found that the error from the single and well‐mixed air zone assumption could be 16% …”
Section: Discussionmentioning
confidence: 99%
“…In using tracer gas measurements to determine airflow rates among zones, we have assumed that each zone could be represented as a single well‐mixed volume. That type of assumption is common in studies of indoor environmental quality; however, its validity is not often scrutinized . In this study, we have explored the extent to which the well‐mixed approximation is a valid representation of the living zone of the studied house and its impact on estimated air change rate values using tracer methods.…”
Section: Resultsmentioning
confidence: 99%
“…That type of assumption is common in studies of indoor environmental quality; however, its validity is not often scrutinized. 4,10,36 In this study, we have explored the extent to which the well-mixed approximation is a valid representation of the living zone of the studied house and its impact on estimated air change rate values using tracer methods. We did so by having a different tracer steadily released in the upper and lower living zones, respectively, for portions of the summer and winter campaigns ( Figures S5 and S6).…”
Section: Mixing Between the Upper And Lower Living Zonesmentioning
confidence: 99%
“…The importance of airflows from the basement to the living area has been noted in both VI and radon studies (Hernandez and Ring, ; U.S. EPA, ). However, most studies have assumed that the whole building, including the basement, is a single and well‐mixed zone (Holford and Freeman, ; Nazaroff et al., ), which likely results in under‐predictions of AERs (Ryswyk et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…EPA, 2003). However, most studies have assumed that the whole building, including the basement, is a single and well-mixed zone (Holford and Freeman, 1996;Nazaroff et al, 1985), which likely results in under-predictions of AERs (Ryswyk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%